LEGAL CONSEQUENCES AND SETTLEMENT OF DOUBLE CERTIFICATES ON LAND PROPRIETARY CERTIFICATES IN AGRARIAN LAW PERSPECTIVE (Study of Complete Systematic Land Registration (PTSL) in Kediri Regency) - Sunardi, Sunardi; Isnaeni, Diyan; Andriyanti, Maritha (Universitas Islam Malang, 2022)
Land is a basic human need that becomes a strategic capital for life. Today, Indonesia has a lot of agendas with agrarian reform. The question of land will never end. With the pattern of land acquisition for development in the public interest along with other land problems, a new body was presented. This body is known as the Land Bank. Land Bank is a special agency (sui generis) which is an Indonesian legal entity established by the central government that is given special authority to manage land. The purpose of the land bank is to create a just economy. As a country of law, there are legals that binding on the subject of land banks. Which legal hierarchy about the land bank. Then this land bank is a new one in Indonesia. Certainly a lot to learn and evaluate the performance of the Land bank agency. The new land bank was established in 2021. Therefore, it is felt to help manage the land bank of Indonesia by making comparisons with other countries, namely the United States. Then the formulation of the problem to be discussed is : (1) How is the arrangement of the establishment of land bank in Indonesia? (2) What are the similarities and differences between land banks in Indonesia and the United States?. Research methods in writing this thesis using the type of normative juridical research, meaning that the problems raised, discussed and described in this study focused on applying the rules or norms in positive law. Approach the problem using the legal approach, conceptual approach, comparative approach to legal materials consisting of primary legal materials, secondary and non-legal materials. The results of this thesis research, first, the regulation of land banks in Indonesia is regulated in the Constitution of Republic Indonesia 1945, UUPA, land procurement law for development for the public interest, job creation law, Government Regulation Number 64 of 2021 on Land Bank, Presidential Regulation Number 113 of 2021 on the structure and Organization of Land Bank. Second, the comparison between land banks in Indonesia and the United States certainly has similarities and differences. The equation is in terms of centralized regulation and the location of the land bank. Differences with the United States lie in regulations, types of land banks, parties to land banks, mechanisms for organizing land banks, and objectives.This study aims and the formulation of the problem is to find out and analyze the Implementation of Complete Systematic Land Registration (PTSL) in Payaman Village, Plemahan District, Kediri Regency, and to find out and analyze the Matters Affecting the Issuance of Multiple Certificates in PTSL in Payaman Village, Plemahan District, Kediri Regency, as well as to find out and analyze the legal consequences and forms of settlement of dual certificates as a result of complete systematic land registration in Payaman Village, Plemahan District, Kediri Regency. This legal research is an empirical legal research. data that Obtained, namely direct research in the field, namely through interviews, then processed and analyzed with descriptive methods using primary data and secondary data. The results of the research on the Implementation of Complete Systematic Land Registration (PTSL) in Payaman Village, Plemahan District, Kediri Regency were carried out through several stages, namely: Preparation, Counseling, Physical Data Collection, Determination of Land Sector, Implementation of Measurements, Measuring Drawings and Mapping of Land Sector, Collection of Juridical Data, Land Inspection, Announcement and Determination of Rights, Bookkeeping of Rights, Issuance and Submission of Certificates. Matters Influencing the Issuance of Multiple Certificates in PTSL in Payaman Village, Plemahan District, Kediri Regency. according to the author there are several factors or reasons for the occurrence of multiple certificates in the implementation of PTSL in Payaman Village, Palemahan District, Kediri Regency, namely: a) Double printed certificates when correcting NIB validation when the SU form is ready, b) Registration of village letter C using letter C of the land next to it c) When the measurement does not participate in witnessing and determining the boundaries of the land it owns, it only depends on the sub-district head who does not know the boundaries, d) Village officials or village officials participate in registering their siblings to become PTSL participants without any authorization from the applicant, e) The applicant hides that the original certificate is brought by his brother on the grounds that a certificate has not been issued which is assisted by village officials. Legal Consequences and Forms of Completion of Multiple Certificates As a result of Complete Systematic Land Registration in Payaman Village, Plemahan District, Kediri Regency resulted in the following: Causing legal uncertainty regarding the certificates they owned. Keywords: Dual Certificate, Village, PTSL.